Phylogenetic analysis and expression profiles of jasmonate ZIM-domain gene family provide insight into abiotic stress resistance in sunflower - Song, Huifang; Fu, Xinxuan; Li, Juan; Niu, Tianzeng; Shen, Jie; Wang, Xi; Li, Yunling; Hou, Qinwen; Liu, Ake (Frontiers in Plant Science, 2022)
JAZ (jasmonate ZIM-domain) proteins act as inhibitory factors of the jasmonic acid (JA) pathway, which is involved in regulating plant development and defense responses. However, there have been no extensive studies available on JAZ genes in sunflower (Helianthus annuus L.). In this study, the phylogenetic analysis of 139 putative JAZ genes from eight plants demonstrated that these JAZs could be divided into five groups (Groups I-V) and 27 sunflower JAZs (HaJAZs) were classified into these five groups. All groups contained genes from both monocotyledons and dicotyledons, indicating that the emergence of JAZ genes predates the differentiation of monocotyledons and dicotyledons. Both segmental and tandem duplications contributed greatly to this gene family expansion in sunflower, especially in Group II. Moreover, the expression profiles of HaJAZ genes under normal conditions, hormone treatments or abiotic stresses were analyzed based on RNA-seq data. HaJAZ2 may be undergoing pseudogenization as a nonfunctional gene because it is not expressed in any tissue. Many HaJAZ genes in roots upregulated their expression when involved in responding to exogenous hormones, especially methyl-jasmonate. The abiotic stress treatments of sunflower showed that HaJAZ5, HaJAZ15, HaJAZ17, HaJAZ20, and HaJAZ21 tend to be sensitive to certain abiotic stresses. HaJAZs from different groups may share similar functions but also exercise their unique functions when responding to abiotic stresses. We speculated that this gene family was conserved in sequence but varied in their expression among duplicated HaJAZ genes, which implies that they may confer neofunctionalization in the adaptation to abiotic stresses; this work provides insight into the resistance of sunflowers and their adaptation to diverse environmental conditions.